Kesulitan belajar dalam bingkai teori Piaget pada siswa SMP usia 13–15 tahun: Systematic literature review: Learning difficulties within the framework of Piaget’s theory among junior high school students aged 13–15 years: A systematic literature review - Mulya, Zhia Ajrin; Kurnia Putri, Indriani Kristanti; Chadjijah, Sitti (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2025)
This systematic literature review addresses the crucial challenge of identifying learning difficulties among junior high school students aged 13-15 through the lens of Piaget's cognitive development theory. The study aims to analyze manifestations of learning difficulties, identify inhibiting factors, and formulate effective intervention strategies based on Piagetian principles. Using the PRISMA 2020 guideline, we conducted a comprehensive analysis of empirical studies from Scopus, Web of Science, ERIC, and other academic databases published between 2005-2025. The results reveal consistent patterns of learning difficulties characterized by dependency on concrete representations, limited abstract reasoning capabilities, and cognitive regression phenomena across mathematics and science subjects. Furthermore, the study identifies significant discrepancies between instructional methods and students' cognitive stages as primary contributing factors. The research concludes by proposing a diagnostic matrix prototype that bridges theoretical Piagetian constructs with practical classroom applications. The findings emphasize the urgent need for cognitive stage-appropriate teaching strategies and have substantial implications for curriculum development, teacher training programs, and educational policy formulation in basic education.